Extrato de alho na quebra do repouso vegetativo de amoreira-preta cultivada organicamente - Dias, João Paulo Tadeu [UNESP]; Carmo, Ezequiel Lopes do [UNESP]; Duarte Filho, Jaime; Ono, Elizabeth Orika [UNESP] (My University, 2011)
We evaluated the application of garlic extract on breaking the vegetative rest of blackberry cv. Tupy, in the period from August to November 2009. The experimental design was randomized blocks with five concentrations of garlic extract and four replications, each plot consisted of two plants, separated by two border plants. The treatments consisted of five concentrations of garlic extract in the form of solution: 0, 1.0, 2.0, 3.0, 4.0 and 5.0% by applying approximately 250 mL per plant. The evaluations were done at 14, 21, 28, 35 and 42 days after treatment, two randomly selected branches in the middle third of the plant being evaluated: the percentage of sprouting, the total number of buds per branch and shoot length. The best results were obtained in higher concentrations of garlic extract, promoting greater anticipation and shoot growth of blackberry. The results indicate the need for studies, which may contribute to increasing the use of garlic extract in the breaking of the dormancy.

Avaliou-se a aplicação de extrato de alho na quebra do repouso vegetativo de amoreira-preta cv. Tupy, no período de agosto a novembro de 2009. O delineamento experimental utilizado foi blocos casualizados, com seis tratamentos e quatro repetições, sendo cada parcela composta por duas plantas, separadas por duas plantas de bordadura. Os tratamentos constaram de seis concentrações de extrato de alho, na forma de solução: 0,0; 1,0; 2,0; 3,0; 4,0 e 5,0% aplicando cerca de 250 mL de solução por planta. As avaliações foram feitas aos 14, 21, 28, 35 e 42 dias após os tratamentos, em dois ramos escolhidos aleatoriamente no terço médio da planta, sendo avaliadas: a porcentagem de brotação, número total de brotos por ramo e comprimento dos brotos. Os melhores resultados foram obtidos em maiores concentrações de extrato de alho, promovendo antecipação e maior crescimento da parte aérea da amoreirapreta. Os resultados apontam a necessidade de mais estudos, os quais podem contribuir para o incremento da utilização do extrato de alho na quebra do repouso vegetativo.
Garlic extract in the break of vegetative repose of blackberry cultivated organically
Keywords: Rubus spp.; Tupy; Vegetative buds; Sprouts; Rubus spp.; Tupy; Desenvolvimento de gemas; Brotação